Perancangan Logo Inilah.Com Dalam Membangun Image Sebagai Portal Media Aktual - Soraya, Iin; Nasir, Ikhwan Muchtar (Komunika: Journal of Communication Science and Islamic Dakwah, 2018)
In the Online Media business competition, a reliable, professional force is needed in presenting fast, precise and accurate news that can be obtained and provide satisfaction for the target audience (readers). That’s why Inilah.com is able to compete with other media portals in the presence of three news strengths here. At the moment Inilah.com needs to design a logo to show the strength that exists in the online media portal. Therefore online media companies really need to have a process in discussing ideas that need to be accepted in order to be more maximal. The research method used is a qualitative method, with the type of research used is qualitative descriptive analysis, data collection methods used are interviews, observation, documentation and literature. The design of Inilah.com logo to give a modern and imaginative impression so that it can enhance the image of this company to its customers and can also attract attention so that it will add readers who want to work together with this company and add the advantages of supported online media companies. It is also something that is sought or made an excuse for consumers to choose Inilah.com as an online information media that is actual and can be trusted by the Indonesian community.